Experimental investigation on hybrid GFRP-concrete decks with T-shaped perforated ribs subjected to negative moment. (15th January 2018) - Zuo, Yize; Liu, Yuqing; He, Jun
Highlights: Proposed a hybrid GFRP-concrete deck system with T-shaped perforated ribs. Experimentally investigated the failure behavior of hybrid decks under negative moment. Simplified calculation methods were proposed to evaluate the strength, crack spacing. Abstract: This paper proposes a hybrid glass fiber reinforced polymer (GFRP)-concrete deck consisting of pultruded GFRP plate with T-shaped perforated ribs in tension part and reinforced concrete in compression part. To better understand the structural behavior of the proposed hybrid deck over main girders in the transverse direction (perpendicular to the traffic direction), static tests on five full-scale deck models were conducted under negative bending moment. The main parameters of these experimental deck models were reinforcement ratio and the presence/absence of bent-up bars. The load-displacement relationship, ultimate capacity, strain distribution of GFRP plates and steel bars, and crack development were measured during the test. Experimental results indicated that flexural and shear failure modes occurred depending on the reinforcement ratio and the presence/absence of bent-up bars. The arrangement of the bent-up bars near the negative moment region can increase the ultimate loading capacity especially with respect to shear strength, but has little influence on the stiffness of the hybrid deck. GFRP T-shaped ribs are effective in controlling cracking. Simplified calculation methods were proposed to evaluate the flexural and shear strength and to predict the average crack spacing, which were calibrated by experimental results. The agreement of theoretical results with experimental ones demonstrates the accuracy and effectiveness of proposed equations for estimating the ultimate capacity and cracking behavior of such hybrid GFRP-concrete decks.